Age at Menarche and Anthropometric Status of School Girls in Rangpur, Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Menarche is a key indicator in pubertal development. This is a biological and social measure of a girl’s healthy transition from childhood into adolescence or young adulthood. Menarche mainly depends on genetic and environmental factors.Objective: The aim of the present study was to observe the prevailing normal menarcheal age and height-weight at that age as well as the correlation between them among the school going girls of Rangpur.Materials and Methods: This cross-sectional descriptive study was carried out from July 2014 to June 2015 among 200, female students (100 rural and 100 urban). Two schools, one from Rangpur city and other from a rural area of Rangpur division were purposively selected for the study. Purpose and procedure of study were explained to the target population and 100 volunteers who had their menstruation started 6 months prior to the time of data collection were selected for the study. Required variables (date of birth, date of menarche, height and weight) were recorded and the data were analyzed using microsoft Excel and SPSS-16.0.Results: The mean menarcheal age in case urban students was 11.8±0.8 years and in case of rural students was 13.6±0.8 years (range: 12-16 years). The mean weight, height and body mass index (BMI) were respectively 46.5 ± 8.4 kg, 153.2 ± 6.6 cm, 19.8 ± 3.2 kg/m2 in urban and 40.0 ± 4.2 kg, 146.4 ± 3.8 cm, 18.6 ± 1.5 kg/m2 in rural subjects. Statistically significant differences were observed at all levels (p